2012
DOI: 10.1016/j.addbeh.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Personality and alcohol use: The role of impulsivity

Abstract: Research has shown that personality traits associated with impulsivity influence alcohol use during emerging adulthood, yet relatively few studies have examined how distinct facets of impulsivity are associated with alcohol use and abuse. We examine the influence of impulsivity traits on four patterns of alcohol use including frequency of alcohol use, alcohol-related problems, binge drinking, and alcohol use disorders (AUDs) in a community sample of young individuals (N = 190). In multivariate regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 55 publications
6
97
1
7
Order By: Relevance
“…A link has also consistently been found between binge drinking and personality traits like impulsivity, disinhibition and sensation/novelty-seeking (Carlson & Johnson, 2012;Czapla et al, 2015;Park, Kim, Gellis, Zaso, & Maisto, 2014;Shin, Hong, & Jeon, 2012;Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014). A recent meta-analysis even found that among different impulsivity-related personality traits (lack of premeditation, lack of perseverance, sensation-seeking, negative urgency, positive urgency, and reward sensitivity) which were positively associated with binge drinking, sensation-seeking had the strongest association across studies (Stautz & Cooper, 2013).…”
Section: Prevalence Of Binge Drinkingmentioning
confidence: 99%
“…A link has also consistently been found between binge drinking and personality traits like impulsivity, disinhibition and sensation/novelty-seeking (Carlson & Johnson, 2012;Czapla et al, 2015;Park, Kim, Gellis, Zaso, & Maisto, 2014;Shin, Hong, & Jeon, 2012;Wellman, Contreras, Dugas, O'Loughlin, & O'Loughlin, 2014). A recent meta-analysis even found that among different impulsivity-related personality traits (lack of premeditation, lack of perseverance, sensation-seeking, negative urgency, positive urgency, and reward sensitivity) which were positively associated with binge drinking, sensation-seeking had the strongest association across studies (Stautz & Cooper, 2013).…”
Section: Prevalence Of Binge Drinkingmentioning
confidence: 99%
“…Drinking to enhance positive emotional states (enhancement motives) has been related to heavy drinking and in turn is linked to certain personality characteristics, such as sensation seeking, 31 low inhibitory control, 32 and impulsivity. 33 Sensation seeking is a personality characteristic that indicates the need for novel experiences and the willingness to take physical and psychological risks for these experiences. 33 The connection of sensation seeking to earlier onset of substance use among teenagers and young adults and to higher levels of substance use has been established.…”
Section: Risk Factors For Binge Drinking In the Context Of Adolescentmentioning
confidence: 99%
“…33 Sensation seeking is a personality characteristic that indicates the need for novel experiences and the willingness to take physical and psychological risks for these experiences. 33 The connection of sensation seeking to earlier onset of substance use among teenagers and young adults and to higher levels of substance use has been established. 34 Lastly, peer use is another important risk factor.…”
Section: Risk Factors For Binge Drinking In the Context Of Adolescentmentioning
confidence: 99%
“…This result might be best explained by the presence of a third, mediating factor, such as impulsivity or sensation-seeking personality traits, which put individuals at an increased risk of both being exposed to ESF and exhibiting binge drinking behaviour [69]. However, the present study did not control for additional confounding factors, which might mediate specific patterns of risky alcohol consumption.…”
Section: Discussionmentioning
confidence: 49%